Pre-injury variables and risk of sport concussion. Issue 11 (25th May 2017) - Mylabathula, Sandhya; Mainwaring, Lynda; Hutchison, Michael; Richards, Doug; Comper, Paul
Abstract : Objective: The study examined whether cognitive functioning, history of concussion (HOC), and sex predicted risk of sport concussion. Design: Retrospective study design. Predictive models were used to determine the predictive ability of each variable. Setting: Canadian University. Participants: 708 data observations from 701 varsity athletes (41.2% female), representing 14 sports. Assessment of risk factors: Two measures of cognitive functioning (mean reaction time and throughput [speed and accuracy]) were assessed using the Automated Neuropsychological Assessment Metrics testing battery. Categorical and continuous measures of HOC, and sex, were examined. Outcome measures: Occurrence of concussion after baseline testing. Main results: HOC was a significant predictor for both sexes. For every previous concussion, the odds of sustaining another concussion increased by 1.5 (95% Confidence Interval [CI]: 1.1, 2.1 [females]; 1.2, 1.9 [males]). Females with a HOC had twice the odds of sustaining another concussion than those without a HOC (CI: 1.1, 4.0). For males, the odds were three times (CI: 1.7, 5.6). Cognitive functioning and sex were not meaningful predictors. Conclusions: This study supports previous findings that HOC is a risk factor and suggests that pre-injury cognitive functioning is not a risk factor for sport concussion. Assessing HOC in all athletes prior to their competitive season provides information regarding their risk of future sport concussion. Thus, it is important for clinicians to record HOC, and to encourage athletes to report concussions to ensure an accurate HOC record. Pre-injury cognitive screening of athletes is not recommended for assessing risk of future concussion. Competing interests: Sandhya Mylabathula, Lynda Mainwaring, and Michael Hutchison None. Doug Richards is the Medical Director at the MacIntosh Sports Medicine Clinic at the University of Toronto Paul Comper is a clinical neuropsychologist consultant with the NHLPA and a member of the Concussion Working Group, but neither were related to the current research